A mechanically interlocked molecular system programmed for the delivery of an anticancer drug1. Issue 4 (16th April 2015) - Barat, Romain; Legigan, Thibaut; Tranoy-Opalinski, Isabelle; Renoux, Brigitte; Péraudeau, Elodie; Clarhaut, Jonathan; Poinot, Pauline; Fernandes, Antony E.; Aucagne, Vincent; Leigh, David A.; Papot, Sébastien
<x xml:space="preserve">Abstract</x> The development of mechanically interlocked molecular systems programmed to operate autonomously in biological environments is an emerging field of research with potential medicinal applications.